Economic growth: The role of knowledge economy in the context of selected Asian countries - Nguyen, Van Dung (University of Economics Ho Chi Minh City, 2023)
This study examines the role of different knowledge economy com-ponents in economic growth as well as the simultaneous effects of information and communication technology (ICT) infrastructure, education, and innovation on economic growth of selected Asian countries over the 1990–2014 period, using Driscoll-Kraay estima-tion method and seemingly unrelated regression (SUR) and three stage least squares (3SLS). The results confirm that there exists a positive association between economic growth and four components of the knowledge economy framework. Furthermore, there is also evidence of the multidimensional effects of ICT infrastructure, edu-cation, and innovation on economic growth. As a result, policy makers should pay more attention to improving innovation, educa-tion, information and communication infrastructure, and institu-tional regime systematically to achieve sustainable economic growth.